Behemoth vs. Leviathan – Thomas Hobbes on the nature of a rebellion (Economic and Political Thought, 2019)
In the article, the author shows the true, empirical foundation of ThomasHobbes’s philosophical and political reflection, justifying his statolatryformulated in Leviathan. In his opinion, Hobbes presents this foundation inthe forgotten and seldom analysed treatise Behemoth, being the narrationabout the events of the English Civil War. In this treatise, Hobbes’s politicalphilosophy meats its social context and history creating the dialectical arrangementconsisting of empirical chaos and philosophical order identified astwo biblical beasts. For this reason both works should be interpreted as partsof a diptych – the philosophical and empirical lecture clarifying the positiontaken in Leviathan. The author also shows that in Hobbes’s opinion the truepower lies not in physical strength, but in force of ideas, which are the realtool in the fight for power.
Keywords: Hobbes, rebellion, Puritan Revolution, English Civil War, Leviathan, Behemoth